Internal Mammarial Lymphoscintigraphy with SPECT after Ultrasound-Guided Injection of 99mTc-Dextran - Ünlü, M.; Ercan, T.M.; Alanyali, H.; Akhan, O.; Bekdik, F.C. (Nuklearmedizin - NuclearMedicine, 1990)
Twenty-two women with stage II or III breast cancer were evaluated by SPECT to determine the number, size, three-dimensional localization and depth from skin surface of the internal mammary lymph nodes for accurate radiotherapy portal planning. The results were also compared with those of planar imaging (PI). Two-step injections of 99mTc-dextran were made under ultrasound guidance into the anterior sheath of the M. rectus abdominis first at the ablation side. 1.5 h thereafter an anterior planar view was obtained to evaluate cross drainage (13.6% was observed). Then, the second injection was done at the opposite side in the same manner. Planar and tomographic images were obtained 1.5 h after the second injection. Similar values were obtained for the depth from skin surface, distance from the midline and diameter of the lymph nodes with both PI and SPECT. The total number of nodes in 22 patients detected by SPECT was higher (138) than that from PI (129), the difference being statistically significant (0.005 > p >0.0005).